2007
DOI: 10.1097/01.brs.0000250979.12398.96
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Lumbar Spondylolisthesis: An Epidemiological Perspective

Abstract: BMI longitudinally and at index evaluations, age, and angle of lordosis were significantly associated with degenerative spondylolisthesis in women. In men, no individual risk factors for degenerative spondylolisthesis were found, save increased age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
199
3
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(225 citation statements)
references
References 24 publications
15
199
3
8
Order By: Relevance
“…As in Cotonou it was 58.6 ± 9.5 years (30 to 77 years), Tagbor et al [15] reported peak at 54 years old in Togo, whereas Bejia et al [18] in Tunisia reported a middle age of 57.9 ± 9.5 years. These findings suggest that degenerative etiology of spondylolisthesis begins in middle age as previously respectively reported by Denard et al [19] and Jacobsen et al [20].…”
Section: Discussionsupporting
confidence: 87%
“…As in Cotonou it was 58.6 ± 9.5 years (30 to 77 years), Tagbor et al [15] reported peak at 54 years old in Togo, whereas Bejia et al [18] in Tunisia reported a middle age of 57.9 ± 9.5 years. These findings suggest that degenerative etiology of spondylolisthesis begins in middle age as previously respectively reported by Denard et al [19] and Jacobsen et al [20].…”
Section: Discussionsupporting
confidence: 87%
“…It is characterized by displacement of one vertebral body over another due to disc degeneration and facet arthropathy, most commonly combined with various degrees of spinal canal stenosis and/or recessal stenosis at the affected level [18]. LDS occurs most frequently at the level of L4/5 and is more common in women and patients over 60 years of age [1,6]. The resulting symptoms are usually a combination of stenotictype radiating buttock and leg pain (LP) and mechanical low back pain (LBP).…”
Section: Introductionmentioning
confidence: 99%
“…There are various reports on the prevalence of spondylolisthesis in different communities. The prevalence among females ranges from 6% in Taiwan to 25% in the US, and among males, from 3% in Taiwan to 31% in the US (6,(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%